Athanasius in Syriac - ter Haar Romeny, Bas (Church history and religious culture, 2010)
This paper discusses aspects of the reception of Athanasius in the Syriac-speaking churches. On the basis of a survey of the Syriac translations of Athanasius and references to him by a number of authors, it is argued that he was considered a very important Father by the Syriac Orthodox, the Melkites, as well as the East Syrians, even though most if not all of the translations were made by the Syriac Orthodox. His status was based not only on the fact that especially in matters of Christology he was considered the epitome of Orthodoxy by all parties, but also on the fact that his ascetic writings formed a major source of inspiration to monks. With the help of five examples the importance of the Syriac tradition for the establishment of critical texts of Athanasius’s writings is shown here to be considerable, even though there are very many issues and problems connected with the translations.